Norman Mailer in Yugoslavia - Potočnik Topler, Jasna (Annales. Series historia et sociologia, 2017)
Norman Mailer (1923-2007) was a prominent American author who, with his works and public criticism, reached far beyond the United States of America. By analysing Mailer's writings and newspaper articles on Mailer, this article examines the role of Norman Mailer in Yugoslavia after WWII. In 1999, Mailer wrote of the attempts by Slobodan Milošević's army to exterminate the Albanians living in Kosovo, and he also criticised President Clinton's decision not to send American ground troops into Kosovo. The role of Mailer in the literary sphere of post-war Yugoslavia was in introducing a new literary movement to Yugoslavia, i. e. literary journalism or, more precisely, new and participatory journalism.
Keywords: 1945/1999; American literature; ameriška književnost; ameriški književniki; Jugoslavija; Literarna recepcija; literarno novinarstvo; Mailer, Norman, 1923-2007; participatory journalism; prevodi v južnoslovanske jezike; translation into South Slavic; Yugoslavia